Estágios refrangentes da experiência humana - Meira, Mônica Birchler Vanzella (2008)
Adolescent behavior is the connecting thread of discussion on the meaning and locus of adult in contemporary society. What are the criteria that define an adult individual? Why his/her behavior? Age groups, rites of passage and relationship between generations are the guides for understanding the condition and definition of social position of an adult person; the myth of hero and the Greek arete affirm their prerogatives; the movie Spring, Summer, Autumn, Winter and... Spring illustrates these concepts. The analysis of other films Mondays in the Sun reveals an important aspect in that apparently extravagant behavior: the demonstration of suffering. Lino's acts confirm this hypothesis. His daily life exposes the rhythm and the demands of our liquid modernity; his attitude is a defensive strategy. The new evidence demands extension of analysis. The legitimation of this model denounces the rite as reinforcement of institutions; qualification as instrument of power and competition, and use of the myth as a way of control. The passage of collective for individual instance, of predicate of subject for verb and the neurotic fixation in youth appear as important elements for the understanding of current times and bring to the light the concept of unigeneration and the reaffirmation of the annihilation rite. The story of Lester Burnham in American Beauty presents a character sensitive to pressure. Lester acts in a similar way to that of Lino, but with an important difference: turning into scapegoat his sad and emancipatory condition allows reconsidering values, references and the position of an adult person